Education data analysis. Strategies and techniques for performing as a preliminary of supervisory action - Castillo García, Manuel; Ramos Corpas, Manuel Jesús; Revuelta Marchena, Manuel (Avances en Supervisión Educativa, 2016)
Supervision of educational institutions should start with the understanding and analysis of a set of variables and with results obtained; in order to achieve this, one must be well- acquainted with the main techniques and tools used in monitoring education. It is a fundamental and mandatory prerequisite to have at your disposal all the necessary information for the teaching centre before setting out to monitor and supervise the specific areas of attention you are dealing with – to this end, using a standardised data analysis system should form part of the education inspector´s recognised supervisory method. In this article we set out an assessment system for educational institutions based on the selection of the principal educational variables.